Preferential transduction of parvalbumin-expressing cortical neurons by AAV-mDLX5/6 vectors - Yazdan-Shahmorad, Padideh; Gibson, Shane; Lee, Joanne C.; Horwitz, Gregory D. (Frontiers in Neuroscience, 2024)
A major goal of modern neuroscience is to understand the functions of the varied neuronal types that comprise the mammalian brain. Towards this end, some types of neurons can be targeted and manipulated with enhancer-bearing AAV vectors. These vectors hold great promise to advance basic and translational neuroscience, but to realize this potential, their selectivity must be characterized. In this study, we investigated the selectivity of AAV vectors carrying an enhancer of the murine Dlx5 and Dlx6 genes. Vectors were injected into the visual cortex of two macaque monkeys, the frontal cortex of two others, and the somatosensory/motor cortex of three rats. Post-mortem immunostaining revealed that parvalbumin-expressing neurons were transduced efficiently in all cases but calretininexpressing neurons were not. We speculate that this specificity is a consequence of differential activity of this DLX5/6 enhancer in adult neurons of different developmental lineages.